A novel pentamethoxyflavone down-regulates tumor cell survival and proliferative and angiogenic gene products through inhibition of IκB kinase activation and sensitizes tumor cells to apoptosis by cytokines and chemotherapeutic agents - Phromnoi K. (2014)
Most anticancer drugs have their origin in traditional medicinal plants. We describe here a flavone, 5,3′-dihydroxy-3,6,7,8,4′- pentamethoxyflavone (PMF), from the leaves of the Thai plant Gardenia obtusifolia, that has anti-inflammatory and anticancer potential. Because the nuclear factor-κB (NF-κB) pathway is linked to inflammation and tumorigenesis, we investigated the effect of PMF on this pathway. We found that PMF suppressed NF-κB activation induced by inflammatory agents, tumor promoters, and carcinogens. This suppression was not specific to the cell type. Although PMF did not directly modify the ability of NF-κB proteins to bind to DNA, it inhibited IκBα (inhibitory subunit of NF-κB) kinase, leading to suppression of phosphorylation and degradation of IκBα, and suppressed consequent p65 nuclear translocation, thus abrogating NF-κB-dependent reporter gene expression. Suppression of the NF-κB cell signaling pathway by the flavone led to the inhibition of expression of NF-κB-regulated gene products that mediate inflammation (cyclooxygenase-2), survival (XIAP, survivin, Bcl-xL, and cFLIP), proliferation (cyclin D1), invasion (matrix metalloproteinase-9), and angiogenesis (vascular endothelial growth factor). Suppression of antiapoptotic gene products by PMF correlated with the enhancement of apoptosis induced by tumor necrosis factor-α and the chemotherapeutic agents cisplatin, paclitaxel, and 5-flurouracil. Overall, our results indicate that PMF suppresses the activation of NF-κB and NF-κB-regulated gene expression, leading to the enhancement of apoptosis. This is the first report to demonstrate that this novel flavone has anti-inflammatory and anticancer effects by targeting the IKK complex. Copyright © 2011 The American Society for Pharmacology and Experimental Therapeutics.